(untitled) (MAUSAM, 2003)
Observed short term (few days to few weeks) variability of mixed layer depth (MLD) and temperature (MLT) at selected locations in the Arabian Sea during pre and summer monsoon seasons is discussed. In the Arabian Sea, pre monsoon season is generally characterized by fair weather conditions with occasional thunder squalls. In the eastern Arabian Sea, SST is above 30° C, which is assumed to be the part of the Indian Ocean warm pool, and is characterized by the diurnal range of about 1.5° C. During the monsoon season, maximum cooling (>l° C) and deepening (5075 m) of the mixed layer is noticed in the central Arabian Sea during the onset phase. On the contrary, the mixed layer shoals in the coastal zones due to upwelling. Miller’s one dimensional mixed layer model is used to simulate the observed mixed layer variability. The model simulated MLT and MLD variations reasonably well on a synoptic scale. Whenever advective processes (horizontal and vertical) and large amplitude waves dominate, significant departures are noticed between the observed and simulated values.